Cephalohematoma Infected With Staphylococcus epidermidis and Skull Abscess: A Case Report - Saeedeh Parvaresh; Maedeh Jafari; Shahryar Eslami; Fatemeh Karami Robati; Mohammad Ali Jafari (Clinical Case Reports)
ABSTRACT Cephalohematoma is a self‐limiting lesion in 1%–2% of neonates. Cephalohematoma bleeds between the bone and periosteum and is limited to cranial sutures. Complications of the cephalohematoma include hyperbilirubinemia and secondary infection. We describe a neonate with cephalohematoma cultures positive for S. epidermidis as well as progressive deepening of the skull. There was no evidence of systemic infection, such as sepsis, meningitis, or osteomyelitis. In the ultrasound and brain MRI, the abscess was restricted to the scalp without involvement of the brain parenchyma and osteomyelitis of the bone. After a short period of intravenous antibiotics and drainage of the abscess, the patient was discharged from the hospital. To our knowledge, this is the first report of cephalohematoma infected with Staphylococcus epidermidis and skull abscess.